Challenges and opportunities for advancing functional MRI in clinical practice - Voets, Natalie L.; Price, Cathy J; Glasser, Matthew F; Benjamin, Christopher; Rutten, Geert-Jan M; Plaha, Puneet; Benzinger, Tammie; Mian, Asim; Gawryluk, Jodie; Pernet, Cyril; Parker Jones, Oiwi; Haller, Sven; et al. (Brain, 2025)
Determining the validity and reliability of a test is paramount when the results inform clinical decision-making. But what are appropriate criteria for tests to predict complex cognitive processing in the brain?Functional MRI (fMRI) was first shown to offer a non-invasive way to indirectly measure neuronal activation in the early 1990s. The first applications in neurosurgery followed within 2 years. As fMRI's use-case expanded, the evidence base widened also. Thirty years later, acceptance of fMRI as a clinical tool varies, with equipoise between those advocating fMRI's benefits as a safe alternative1 and those highlighting its shortcomings compared to invasive clinical tests.2 Should the goal for fMRI be to perfectly mimic (admittedly imperfect) clinical ‘gold standards’, or to complement these by improving performance outcomes? In other words, how should fMRI's adequacy be defined? Focus is often placed on demonstrating reproducibility. In this light, a fundamental challenge for clinical validation is the many ways to acquire, analyse and interpret fMRI data measuring cognitive processes, which are rarely exactly reproducible.
Veröffentlicht: 18. Februar 2025
Gesehen am 25.09.2025